Design and Optimization of Discone Antenna for Medical Device Electromagnetic Interference Measurement - Haryo Dwi Prananto; Dwi Mandaris; Aditia Nur Bakti; Achmad Munir (Jurusan Teknik Elektro, Fakultas Teknik, Universitas Negeri Semarang, 2023)
The wide spread of the Internet of Things creates the possibility of electromagnetic interference in medical devices. Therefore, it is necessary to perform risk mitigation by finding the value of electromagnetic interference through measurements using wideband and omnidirectional antennas, e.g., the discone antenna. In this research, the optimization of the S11 value of a designed discone antenna was obtained using simulation from the effect of dimensional variations in discone parameters like disc diameter, cone bottom diameter, gap, and cone height on S11 characteristics. The parameters were combined for optimization. The design was fabricated, and the S11, radiation pattern, gain value and antenna factor, and the ability to measure interference through modeling were measured. Gain value and antenna factor were obtained using the gain-comparison method, which compared the antenna of interest against another antenna with a standard gain. The optimization was successfully performed with a better S11 value. At 5.2 GHz, the value of S11 was below -10 dB. The realization of the design showed similar results to the simulation, and it was found to be able to operate in the medical device frequency range (wideband). The ability of the discone antenna improved in terms of S11 value, especially at 5.2 GHz, where the value was below -17.443 dB. The radiation pattern of the designed antenna is omnidirectional. Additionally, validation was carried out by providing gain value and antenna factor. It has been proved that the designed discone antenna could measure interference successfully by modeling interference sources as electric field sources from all directions.